The status of potable water reuse implementation - Jeffrey, P.; Yang, Z.; Judd, S.J. (Water research (Oxford), 2022)
•Status of implementation of wastewater treatment for reuse as potable water reviewed.•>50% of all schemes use RO followed by UV disinfection, a few with UV AOP final step.•QMRA studies show risk imposed by controlled reuse smaller than from de facto reuse.•Implementation becomes challenging if unbounded environmental waters used as buffers.•Pivotal requirement is reliable, on-line monitoring of pathogens and key CECs. A review of the current status of direct and indirect potable water reuse (DPR/IPR) implementation has been conducted, focusing on the regulatory and practical aspects and with reference to the most recent published literature. The review encompasses (a) the principal contaminant types, their required removal and the methods by which their concentration is monitored, (b) regulatory approaches and stipulations in assessing/ratifying treatment schemes and maintaining treated water quality, and (c) existing full-scale installations. Analytical methods discussed include established in-line monitoring tools, such as turbidity measurement, to more recent polymerase chain reaction (PCR)-based assay methods for microbial detection. The key risk assessment tools of quantitative microbial risk assessment (QMRA) and water safety plans (WSPs) are considered in relation to their use in selecting/ratifying treatment schemes, and the components of the treatment schemes from 40 existing IPR/DPR installations summarised. Five specific schemes are considered in more detail. The review reveals:1over half of the schemes identified employ reverse osmosis (RO) followed by UV disinfection, with UV-based advanced oxidation used in many modern schemes as the final step;2Whilst quantitative PCR appears to offer many advantages for microbial detection, due to its sensitivity and specificity, it nonetheless demands pre-concentration of the sample and is subject to interference leading to possible false positives;3QMRA studies suggest that the risk imposed by DPR and, in particular, IPR is very small compared with de facto reuse, the latter being subject to far less regulatory scrutiny;4There appears to be no evidence of acute conditions, and diarrhoeal disease specifically, from the few epidemiological studies which have been conducted; and.5IPR implementation becomes challenging if unbounded environmental waters are used as a buffer, since “zero deterioration” in environmental quality must then be demonstrated.Whilst there are a number of ongoing projects where RO is not used because of the challenge imposed by disposal of RO concentrate, the prevalence of the sequential RO-UV combination implies the importance of quantifying the impact of process upsets on these unit operations. [Display omitted]